Swift: A Hybrid Digital-Analog Scheme for Low-Delay Transmission of Mobile Stereo Video - Luo, Chong; Wu, Feng; Zeng, Wenjun (Proceedings of the 18th ACM International Conference on Modeling, Analysis and Simulation of Wireless and Mobile Systems, 2015)
Efficient and robust wireless stereo video delivery is an enabling technology for various mobile 3D applications. Existing digital solutions have high source coding efficiency but are not robust to channel variations, while analog solutions have the opposite characteristics. In this paper, we design a novel hybrid digital-analog (HDA) solution to embrace the advantages of both solutions and avoid their drawbacks. Basically, in each pair of stereo frames, one frame is digitally encoded to ensure basic quality and the other is analogly processed to opportunistically utilize good channels for better quality. To improve the system efficiency, we design a zigzag coding structure such that both intra-view and inter-view correlations can be explored through prediction in the frames to be analogly coded. A reference selection mechanism is proposed to further improve the coding efficiency. In addition, we address the problem of optimal power and bandwidth allocation between digital and analog streams. We implement a system, named Swift, and perform extensive trace-driven evaluations based on a software-defined radio platform. We show that Swift outperforms an omniscient digital scheme under the same bandwidth and power constraints, or can have around 2x power saving in order to achieve comparable performance. Subjective quality assessment evidences that Swift provides significantly better visual quality than a straightforward HDA extension of SoftCast.